Identification of CDC42 Effectors Operating in FGD1-Dependent Trafficking at the Golgi - Egorov, Mikhail; Polishchuk, Roman (Frontiers in Cell and Developmental Biology, 2019)
Loss of function mutations in FGD1 gene causes a rare X-linked disease - faciogenital dysplasia (FGDY, also known as Aarskog-Skott syndrome), which is associated with bone and urogenital abnormalities. FGD1 encodes а CDC42-specific guanine nucleotide exchange factor. We have been previously reported that Golgi-associated FGD1 regulates the post-Golgi transport of some conventional and bone specific proteins in CDC42-dependent manner. However, which downstream targets of FGD1/CDC42 signaling operate to support transport from the Golgi, remains elusive. Here, we demonstrated that Golgi-localized CDC42 effectors *** are involved in FGD1-mediated post-Golgi transport probably through coordination of Golgi membrane and cytoskeleton dynamics. This provides new insights in understanding the molecular mechanisms behind FGD1/CDC42-dependent trafficking events in pathogenesis of FGDY.